Deformation of oxide scale and surface roughness transfer during hot rolling of stainless steel 304L. (9th November 2009) - Wei, Dongbin; Huang, Junxia; Zhang, Aiwen; Jiang, Zhengyi; Tieu, A.; Wu, Fei; Shi, Xu; Jiao, Sihai
The oxidation characteristic of stainless steel 304L in humid air and the deformation behaviour of the oxide scale during hot rolling at 1050°C were investigated. The surface roughness transfer during hot rolling was discussed. With an increase of reduction, the oxide scale thickness decreases linearly, the surface roughness also decreases obviously and the integrity of oxide scale increases. The thickness decrease of thick oxide scale is more rapid than a thin oxide scale. The surface roughness always decreases with an increase of reduction, and the oxide scale thickness affects the surface roughness transfer during hot rolling.